Consistency Between Beliefs and Behavior Regarding Use of Substances in Recovery. (13th March 2015) - Kaskutas, Lee Ann; Ritter, Lois A.
This article addresses the assumption that pathways to recovery from substance abuse and dependence, and the language used to define one's relationship to substances, translate to actual beliefs and behaviors in terms of substance use. We draw on social representation theory and use data from a large web-based study ( N = 9, 341) whose goal was to understand how individuals in recovery define what recovery means to them. We often hear people say that they are "in recovery, " and present findings now provide empirical evidence of the prevalent meanings of this ubiquitous expression. The belief that recovery is abstinence was broadly held in our sample, especially among those exposed to treatment and 12-step self-help groups and who define themselves as in recovery —and most (but not all) of such individuals are complete abstainers (no alcohol or drugs). In contrast, among the "self-changers" who did not attend treatment or self-help groups, the most common self-definition was used to have an alcohol or drug problem but don't any more, half of whom believe that recovery is abstinence while half do not, and only one third are abstainers. Findings are of public health relevance, as it is estimated that among American adults alone, 10% report having had alcohol or drug problems but no longer do. In line with the central concepts of social representation theory, people's pathways to recovery have a strong effect on how they define themselves and their behaviors and beliefs, but it is not universal.